Inclusion of brain volume loss in a revised measure of 'no evidence of disease activity' (NEDA-4) in relapsing-remitting multiple sclerosis - Kappos, Ludwig; De Stefano, Nicola; Freedman, Mark S; Cree, Bruce Ac; Radue, Ernst-Wilhelm; Sprenger, Till; Sormani, Maria Pia; Smith, Terence; Häring, Dieter A; Piani Meier, Daniela; Tomic, Davorka (Multiple sclerosis, 2016)
'No evidence of disease activity' (NEDA), defined as absence of magnetic resonance imaging activity (T2 and/or gadolinium-enhanced T1 lesions), relapses and disability progression ('NEDA-3'), is used as a comprehensive measure of treatment response in relapsing multiple sclerosis (RMS), but is weighted towards inflammatory activity. Accelerated brain volume loss (BVL) occurs in RMS and is an objective measure of disease worsening and progression. To assess the contribution of individual components of NEDA-3 and the impact of adding BVL to NEDA-3 ('NEDA-4') METHODS: We analysed data pooled from two placebo-controlled phase 3 fingolimod trials in RMS and assessed NEDA-4 using different annual BVL mean rate thresholds (0.2%-1.2%). At 2 years, 31.0% (217/700) of patients receiving fingolimod 0.5 mg achieved NEDA-3 versus 9.9% (71/715) on placebo (odds ratio (OR) 4.07; p < 0.0001). Adding BVL (threshold of 0.4%), the respective proportions of patients achieving NEDA-4 were 19.7% (139/706) and 5.3% (38/721; OR 4.41; p < 0.0001). NEDA-4 status favoured fingolimod across all BVL thresholds tested (OR 4.01-4.41; p < 0.0001). NEDA-4 has the potential to capture the impact of therapies on both inflammation and neurodegeneration, and deserves further evaluation across different compounds and in long-term studies.